Contribution of mutations in gyrA and parC genes to fluoroquinolone resistance of mutants of Streptococcus pneumoniae obtained in vivo and in vitro. - Tankovic, J (1996)
We have analyzed by gene amplification and sequencing mutations in the quinolone resistance-determining regions of the gyrA, gyrB, and parC genes of fluoroquinolone-resistant Streptococcus pneumoniae mutants obtained during therapy or in vitro. Mutations leading to substitutions in ParC were detected in the two mutants obtained in vivo, BM4203-R (substitution of a histidine for an aspartate at position 84 [Asp-84-->His]; Staphylococcus aureus coordinates) and BM4204-R (Ser-80-->Phe), and in two mutants obtained in vitro (Ser-80-->Tyr). An additional mutant obtained in vitro, BM4205-R3, displayed a higher level of fluoroquinolone resistance and had a mutation in gyrA leading to a Ser-84-->Phe change. We could not detect any mutation in the three remaining mutants obtained in vitro. Total DNA from BM4203-R, BM4204-R, and BM4205-R3 was used to transform S. pneumoniae CP1000 by selection on fluoroquinolones. For the parC mutants, transformants with phenotypes indistinguishable from those of the donors were obtained at frequencies (5 x 10(-3) to 8 x 10(-3)) compatible with monogenic transformation. By contrast, transformants were obtained at a low frequency (4 x 10(-5)), compatible with the transformation of two independent genes, for the gyrA mutant. Resistant transformants of CP1000 were also obtained with an amplified fragment of parC from BM4203-R and BM4204-R but not with a gyrA fragment from BM4205-R3. All transformants had mutations identical to those in the donors. These data strongly suggest that ParC is the primary target for fluoroquinolones in S. pneumoniae and that BM4205-R3 is resistant to higher levels of the drugs following the acquisition of two mutations, including one in gyrA.